At the dawn of the White Movement (about A. S. Puchenkov’s monograph «The first year of the Volunteer Army: from the emergence of the “Alekseevskaya Organization” to the formation of the Armed Forces in the South of Russia (November 1917 – December 1918)») - D. A. Bazhanov (Омский научный вестник: Серия "Общество. История. Современность")
The author analyzes A. S. Puchenkov’s monograph «The first year of the Volunteer Army: from the emergence of the “Alekseevskaya Organization” to the formation of the Armed Forces in the South of Russia (November 1917– December 1918)». There is no doubt about the relevance of the plot chosen by A. S. Puchenkov, which is confirmed by the ongoing scientific discussion reflected in the monographs and articles analyzed by the researcher. The author’s balanced approach to the consideration of a number of complex issues of the Civil War in Russia is noted. He critically comprehends the causes and circumstances of the birth of the counterrevolution, and shows both the strengths and weaknesses of the emerging White Movement. The author concluded that the book by A. S. Puchenkov allows to get a comprehensive picture of the military and political formation of the White Movement in the South of Russia, highlights the main factors for the success of the counter-revolution in 1918, presents vivid portraits of its leaders, revealing their difficult relationships. Of particular importance is the disclosure of the role of the correlation of regional separatism and all-Russian state patriotism in the subsequent defeat of the Whites. Some critical notes that show the following ways of research on the basis of the Russian Civil War are made.